Aggressiveness of modern youth: causes and ways of prevention (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article considers the phenomenon of aggression in thecontext of human nature. Such concepts as aggression and aggressivenessare considered, the urgency of this phenomenon and its conditioned factorsare determined, the methods to determine the level of aggressivenessamong modern youth are conducted. Factors of aggressive behavior amongteenagers are described. Notion such as «cyberbullying» are explained.The main types of aggression have been defined and the main functionsand types of aggressive behavior in teenagers have been identified. Factorscausing the increase in the level of aggressiveness are also noted. The resultsof the research between boys and girls are demonstrated. Psychologicaland pedagogical recommendations on their identification and prevention.were proposed and developed.
Keywords: the phenomenon of aggression; aggression; aggressiveness; «cyberbullying»; aggressive behavior; boys; girls; teenagers.